?SOLID STATE COPOLYMERIZATION OF ACRYLAMIDE AND CINNAMIC ACID UNDER UV RADIATION (Biological Sciences - PJSIR, 2000)
Solid state copolymerization of acrylamide (r.) and cinnamic acid (r2) was accomplished under UV radiation at a tem- perature 68°C below the melting point of monomers. It is noted that yield of the product does ~ot repeat but trend remains the same. The monomer reactivity ratios were determined to be rl=I.6 and r2= O. Molecular weights of the product samples range between 11205 -72770. All copolymer samples are off-white solid substances that become light yellow at 140°C.